DZIAŁALNOŚĆ CHARYTATYWNA WYZWANIEM DLA PARAFII - Nogowski, Jacek Marek (Civitas et Lex, 2015)
Charity activity in the parish it is a charity service based on the God’s commandment of love, appropriate to needs of people who suffer financial or spiritual poverty, aimed at bringing help in living decent quality of life. The motive for activity and the charity service comes out of the commandment of the love to a neighbor and desire for imitating the Christ (Luke 10,30−36). Service to poor and suffering people is an evidence of faithfulnesses to the Gospel and is a continuation of the rich charity tradition of the Roman Catholic Church. Concern about the poor and needing people carried on in the organized and scheduled way exemplifies the solidarity in the Christ with the poor people.